Cover Image. (16th June 2021) - Abbasi, Nimrah; Moore, Aideen; Chiu, Priscilla; Ryan, Greg; Weksberg, Rosanna; Shuman, Cheryl; Steele, Leslie; Chitayat, David
Abstract : The cover image is based on the Original Article Prenatally diagnosed omphaloceles: Report of 92 cases and association with Beckwith‐Wiedemann syndrome by Nimrah Abbasi et al., https://doi.org/10.1002/pd.5930 .